2022
DOI: 10.1101/2022.02.02.478784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contact networks have small metric backbones that maintain community structure and are primary transmission subgraphs

Abstract: The structure of social networks strongly affects how different phenomena spread in human society, from the transmission of information to the propagation of contagious diseases. It is well-known that heterogeneous connectivity strongly favors spread, but a precise characterization of the redundancy present in social networks and its effect on the robustness of transmission is still lacking. This gap is addressed by the recently introduced metric backbone, a subgraph that is sufficient to compute all shortest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The metric backbone is the subgraph that is sufficient to compute all shortest paths in the network, thus removing edges that break the triangle inequality (and are therefore redundant in regards to the shortest paths). This network retains all metric edges and preserves all the nodes in the original network 12,13 . Considering that a set of the PPI in each layer are evolutionarily-conserved, we developed the orthoBackbone: a single shared subnetwork obtained by collapsing the metric backbone of all layers according to the orthologous relationships.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metric backbone is the subgraph that is sufficient to compute all shortest paths in the network, thus removing edges that break the triangle inequality (and are therefore redundant in regards to the shortest paths). This network retains all metric edges and preserves all the nodes in the original network 12,13 . Considering that a set of the PPI in each layer are evolutionarily-conserved, we developed the orthoBackbone: a single shared subnetwork obtained by collapsing the metric backbone of all layers according to the orthologous relationships.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that it is possible to simplify the complexity of biological networks by removing network redundancy as to only retain the key edges that sustain the system 24 . These edges form the network backbone and are calculated based on the minimum number of shortest paths (proxy to the most relevant interactions) required to maintain network integrity 25 . In the context of transcriptome networks, the backbone uncovers the essential gene interactions that define core pathways in the gene expression program 26 .…”
Section: Figurementioning
confidence: 99%
“…The metric backbone is a subgraph that is sufficient to compute all shortest paths in the network, thus removing edges that break the triangle inequally (and are therefore redundant regarding the shortest paths). This network retains all metric edges and preserves all the nodes in the original network [36, 115]. We have previously used the metric backbone of transcriptome networks to identify biologically relevant genes and their interactions [37].…”
Section: Methodsmentioning
confidence: 99%